2005
DOI: 10.1111/j.1447-0756.2005.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of the regression of the placenta left in situ in an advanced abdominal pregnancy using the Cavalieri method

Abstract: In this abdominal pregnancy, the dead fetus was delivered through an abdominal incision at the 36th gestational week. The placenta invaded the small intestine and the omentum was left in situ. The placental degeneration was monitored using serial serum beta-human chorionic gonadotropin values. In certain periods, the follow up of the placental regression was carried out using the Cavalieri method with abdominal ultrasound. It was seen that the placental volume had decreased by 83% at the end of 1 year. To the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…Cuando no es posible la extracción placentaria completa, dejar la placenta in situ es una opción, y debe considerarse el seguimiento estricto por la posibilidad de complicaciones maternas como abscesos, hemorragias tardías y obstrucciones de vísceras huecas, producto de fenómenos inflamatorios y necróticos secundarios (15) . El metotrexato para el manejo postoperatorio de la reducción placentaria es discutido.…”
Section: Discussionunclassified
“…Cuando no es posible la extracción placentaria completa, dejar la placenta in situ es una opción, y debe considerarse el seguimiento estricto por la posibilidad de complicaciones maternas como abscesos, hemorragias tardías y obstrucciones de vísceras huecas, producto de fenómenos inflamatorios y necróticos secundarios (15) . El metotrexato para el manejo postoperatorio de la reducción placentaria es discutido.…”
Section: Discussionunclassified
“…The review by Nahum showed that 50% of pregnant uterine horns rupture, and of all the ruptures, 13%, 67%, and 20% occurred during the first, second and third trimester, respectively 16 . Although early diagnosis of rudimentary horn pregnancy has recently increased in frequency, there are still many cases that remain undiagnosed until later stages or until the time of delivery 18–23 …”
Section: Discussionmentioning
confidence: 99%
“…Other reported sequalae include paralytic ileus, secondary haemorrhage, disseminated intravascular coagulation, 5 return to theatre, 19,63,64 fistulae formation, 65 persistent hydronephrosis 66 and protracted hospital stay. This approach also requires follow up with regular ultrasound scans and/or serum beta‐human chorionic gonadotrophin (bhCG) levels to assess placental involution 36 . Although structural involution can be very slow (up to 5.5 years), the hormonal function declines more rapidly (10 days to 7 weeks) 30,41,67 …”
Section: The Placentamentioning
confidence: 99%
“…This approach also requires follow up with regular ultrasound scans and/or serum beta-human chorionic gonadotrophin (bhCG) levels to assess placental involution. 36 Although structural involution can be very slow (up to 5.5 years), the hormonal function declines more rapidly (10 days to 7 weeks). 30,41,67 To accelerate resorption when the placenta is left behind, methotrexate has been administered, but cannot be routinely recommended because of a significant risk of infection.…”
Section: Management Of the Placentamentioning
confidence: 99%